β-blockades and the risk of atrial fibrillation in patients with cardiovascular diseases - Gu, Xun-Hu; Li, Weichao; Li, Heng; Guo, Xun; He, Jiang; Liu, Yuyan; Gong, Jianping; Huang, Yizhou; Zhang, Bin (Frontiers in Pharmacology, 2024)
β-blockers have been widely used in patients with extensive cardiovascular disease (CVD) and have provided benefits. However, they are more likely to cause symptomatic bradycardia, hypotension, or glucose metabolism disorders, which may lead to an increased risk of atrial fibrillation (AF), but evidence is lacking.This study was to analyze the association between the use of β-blockers and the risk of developing AF.This nationwide, prospective cohort study utilized data from the 2013-2020 National Health and Nutrition Examination Survey (NHANES). The patients were stratified into a β-blocker treatment group (n=2585) and a non-β-blocker treatment group (n=8525). Univariate and multivariate logistic regression analyses were performed to identify the relationship between β-blockades and the risk of AF. Propensity matching analysis was used to balance patient baseline characteristics and to control for confounders.A total of 11,110 subjects were included in this study (mean [SD] age, 59.89 [15.07] years; 5657 [49.7%] males). A total of 111/2585 subjects developed AF in the β-blocker treatment group, and 75/8525 developed AF in the non-β-blocker treatment group (incidence rate, 4.2% vs. 0.8%). Compared with the non-β-blocker group, the β-blocker group had an increased risk of incident AF (aOR, 2.339; 95% CI, 1.614-3.410). Some sensitivity analyses also revealed consistent findings of increased AF risk associated with β-blocker treatment.The findings from this study suggest that β-blocker treatment is associated with an increased risk of incident AF and may help physicians select a modest medication for patients while also assessing the risk of AF.